Hubungan Tingkat Pengetahuan dan Sikap Tentang Keputihan dengan Kejadian Keputihan pada Siswi Kelas VIII SMPN 5 Pangkalpinang Tahun 2025 - Juwita Juwita; Sri Hastini Jaelani; Shandy Kusumawardani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Vaginal discharge is a reproductive health problem that commonly occurs in adolescent women and can be influenced by the individual’s level of knowledge and attitude towards intimate organ hygiene. Lack of understanding can increase the risk of pathological vaginal discharge. This study aims to determine the relationship between knowledge and attitudes towards the incidence of vaginal discharge in adolescent women. Based on data obtained from a research study conducted at SMPN 5 Pangkalpinang class VIII in February 2025, 7 out of 10 female students have experienced vaginal discharge. This means that most of the eighth grade female students who have experienced puberty experience whiteness in their lives. This research uses a quantitative design with a cross-sectional approach. The sample consisted of 68 respondents selected using purposive sampling technique. Data was collected through a structured questionnaire which had been tested for validity and reliability. Data analysis was carried out using the Chi-Square test. The research results showed that 57 (83.8%) respondents had experienced vaginal discharge, while the other 11 respondents (16.2%) had never experienced vaginal discharge. In the knowledge variable, 51 (75%) respondents had low knowledge, 13 (19.1%) had sufficient knowledge and the remaining 4 (5.9%) had high knowledge, while for the attitude variable 55 (80.9%) had a negative attitude, 13 (19.1%) other respondents had a positive attitude towards the incidence of vaginal discharge at SMPN 5 Pangkalpinang. The results of this study indicate that there is a significant relationship between knowledge and attitudes towards vaginal discharge with a Sig value of p = .000 < 0.05.It is recommended that the SMPN 5 Pangkalpinang school provide education, promotion or health education about the incidence of vaginal discharge, so that it can improve the health status of teenagers. And for educational institutions to further deepen students’ knowledge of health by increasing knowledge about the incidence of vaginal discharge, especially in adolescents.